General Practitioners Viewpoints about Continuous Medical Education Programs - Ali Koosha; Nahid Kazemizanjani; Abass ali Nourian; Nouredin Mousavinasab (Kerman University of Medical Sciences, 2010)
Background & Objective : Need assessment is can be applied as a tool for a better usage by managers and designers of Continuous Medical Education (CME) programs Hence this study was conducted to assess general practitioners viewpoints about Continuous Medical Education Programs held in Zanjan University of Medical Education Methods : This descriptive study was conducted on all general practitioners of Zanjan province (450 persons) but only 260 ones participated by filling in the questionnaires Results : The motive to participate in CME programs in 462% of the participants was gaining credit points while updating scientific information was reported in 388% of them 588 percent of the physicians believed that the effect of CME programs was moderate to high 565% wanted 5 to 10 CME programs a year The influence of CME programs place was high to very high according to 642% of the participants 512 percent preferred weekends whereas 407% preferred daily fourhour programs 588 percent were in favor of holding pretests and posttests to determine the qualitative effect of the program Conclusion : According to general practitioners CME programs could be more effective So it is recommended to hold these programs at the weekends one day a week and four hours a day Five to ten programs are also suggested in a year